TOLERANCE OF MUNG BEAN (Vignaradiata (L.) Wilczek) TO LACTIC ACID, A POTENTIAL HERBICIDE: GROWTH AND MORPHOLOGY - Derick Erl P. Sumalapao; Caireen G. Tuppil; Anton Angelo C. Urtula; Duane M. Valdestamon; Leoncia Marie D. Villanueva; Nadine Adellia A. Ledesma (Journal of Animal and Plant Sciences, 2018)
Lactic acid is used as an environmentally safe herbicide against a variety of grass and broadleaf weed species. However, it was found to be toxic to certain leguminous weeds and may also be toxic to important legume crops including mung bean. The effect of varying concentrations of lactic acid on the growth and morphological characteristics of two types of mung bean seedlings was determined to test the possibility of its safe use on the crop. Our findings show that although an 8% lactic acid concentration was toxic to both types of mung bean, they differed in their tolerance to lower concentrations in terms of root and shoot length and fresh and dry weight of roots and shoots. Minimum tolerance was observed at 2% lactic acid for both mung bean types. These tolerable concentrations are already much higher than those reported to be toxic to certain weed species, indicating that high concentrations of lactic acid may be safe to use on mung bean. The findings of this research can provide relevant information on the potential use of lactic acid as an organic herbicide and its possible effects on the growth of mung beans as well as other important legume crops.
Keywords: Lactic acid; Plant growth regulation; Vignaradiata; Mung bean; Plant morphology; Biopesticide; Herbicide; Weed management